Influences of work motivation, leadership effectiveness and time management toward job performane among lower level management at Operation Department Of Election Commission Malaysia, Putrajaya / Rosma Shafinie Yusof...[et al] - Yusof, Rosma Shafinie (Faculty of Business and Management, 2012)
This study is to examine the influences of work motivation, leadership effectiveness and time management towards jo b performances among lower level management at Operation Department of Election Commission Malaysia, Putrajaya. Election Commission Malaysia is functioning to uphold the system of parliamentary democracy and protect the right of the people to elect their representative by managing, conducting and supervising election in a fair and free manner. Election Commission of Malaysia was established on 4 September 1957 in accordance with Article 114 of the Federal Constitution. During the estab lishment of the Election Commission it consists of a Chairman and 2 Members. The first Chairman of the Commission's is Y.Bhg. Dato 'Dr.Albakri bin Haji Hassan Mustafa, while the members consist of Mr. Lee Ewe Boon and Mr Ditt Singh. Since its inception in 1957 until 1978, the Commission Headquarters located in Sultan Abdul Samad Building, Clark Road, Kuala Lumpur and currently the Commission Headquarters have moved to present location in Putrajaya since year 2000. Job performances are a prestige indicator that every employee can reach and it reflects the degree of a successful leader. Past studies by Tiena and Putri, (2007) shows that the employee job performances is the most wanted result that every organization expected form the employee personal behavior.